The Effects of Integrating Digital Storytelling to Students’ Motivation - Reza Anggriyashati Adara; Aridhotul Haqiyyah (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2020)
Incorporating technology seems to have positive effects on improving students’ motivation on EFL (English as a Foreign Language) learning. One of strategies that can be used to improve students’ motivation in EFL classrooms is incorporating digital storytelling or an amalgamation of audio, text, animation and voice. Therefore, the present study aims to analyse the effects of digital storytelling to motivation of a group of Indonesian EFL learners. The present study applied a quasi-experiment design. The participants of present study are 19 college students whom are divided into experimental and control classes. In order to obtain the results, a set of questionnaires adapted from Deci & Ryan’ Self Determination Theory (2002) and Yoon’s (2013) toward digital storytelling motivation are distributed to the participants. Besides that, semi-structured interviews were conducted to two students to provide deeper insights toward the effects of digital storytelling on students’ motivation. In addition, English tests were given before and after the treatment. The results show that the experimental class shows slightly higher level of motivation than the control class. In addition, the respondents considered digital storytelling as beneficial for improving their English skills and creativity. Besides that, students in experimental class performed better in English test than ones in control class after treatment. Thus, it can be said that digital storytelling seems to have positive effects on students.